Prevalence and causes of social media usage and addiction status of pregnant women - Merve Bağrici Bozan; Eda Cangöl (BMC, 2023)
Abstract Background This study was conducted to determine the prevalence and causes of social media usage and the addiction status of pregnant. Materials and methods This cross-sectional study, which was conducted in the Gynecology and Obstetrics Clinics of a university and state hospital between December 2019 and February 2020 in a city in the west of Turkey, aims to determine the prevalence and causes of social media usage and the addiction status of pregnant women. 500 people were included in the study. The data were collected with the face-to-face interview technique in the outpatient clinics. Results The prevalence of the pregnant women's social media usage was found to be 100%. The average daily social media usage was 3.5 h, whereas the social media addiction index was X̅ = 65.58. There were 358 pregnant women (71.6%) with high social media addiction scores. Conclusions In the study, it was concluded that all the pregnant women used social media and that most of them had a high level of social media addiction. Healthcare professionals should promote the conscious and balanced use of social media by organizing educational programs related to the accessibility of accurate and reliable online content for pregnant women at every stage of healthcare, and the dangers and addiction of social media.